Broker routing decisions in limit order markets - David A. Cimon (Bank of Canada, 2016)
The primary focus of this paper is to study conflict of interest in the brokerage market. Brokers face a conflict of interest when the commissions they receive from investors differ from the costs imposed by different trading venues. I construct a model of limit order trading in which brokers serve as agents for investors who wish to access equity markets. I find that brokers preferentially route marketable orders to venues with lower liquidity demand fees, driving up the execution probability at these venues and lowering adverse selection costs. When fees for liquidity supply and demand are sufficiently different, brokers route liquidity supplying orders to separate venues, where investors suffer from lower execution probability and higher costs of adverse selection.
Keywords: G24; G28; 330; Financial markets; Market structure and pricing